ARLETTE FARGE, The Allure of the Archives - Millar, Laura (Archivaria, 2015)
The Allure of the Archives. ARLETTE FARGE. Translated by Thomas Scott-Railton. Foreword by Natalie Zemon Davis. New Haven & London: Yale University Press, 2013. xvi, 131 pp. ISBN 978-0-300-17673-5.